2007
DOI: 10.1051/gse:2007024
|View full text |Cite
|
Sign up to set email alerts
|

NNATandDIRAS3genes are paternally expressed in pigs

Abstract: -Although expression and epigenetic differences of imprinted genes have been extensively characterised in man and the mouse, little is known on livestock species. In this study, the polymorphism-based approach was used to detect the imprinting status of NNAT and DIRAS3 genes in five heterozygous pigs (based on SNP) of Large White and Meishan F 1 hybrids. The results show that both genes were paternally expressed in all the tested tissues (heart, liver, spleen, lung, kidney, stomach, small intestine, skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…In pigs, a few imprinted genes have been found to be expressed monoallelically in somatic tissues [8], [9]. Recently, we and others have confirmed the methylation patterns of IGF2/H19 DMRs in preimplantation embryos and in primordial germ cells, respectively [10], [11].…”
Section: Introductionsupporting
confidence: 52%
“…In pigs, a few imprinted genes have been found to be expressed monoallelically in somatic tissues [8], [9]. Recently, we and others have confirmed the methylation patterns of IGF2/H19 DMRs in preimplantation embryos and in primordial germ cells, respectively [10], [11].…”
Section: Introductionsupporting
confidence: 52%
“…In the pig, a study showed that NNAT was imprinted in 11 tissues, including heart, liver, spleen, lung, kidney, stomach, small intestine, skeletal muscle, fat, uterus, ovary, and pituitary gland [12], but in pig placenta, the expression status inherited from parents was still uncovered to our knowledge.…”
Section: Introductionmentioning
confidence: 98%